Vitamin supplementation improves the adaptive response of skeletal muscle to repeated eccentric exercise-induced muscle damage - Bergin, P. M.; Warmington, S. A. (The Journal of Physiology, 2002)
Unaccustomed eccentric exercise can damage active skeletal muscle, causing a reduction in force output (Brown et al. 1997). However, a single bout of eccentric exercise can produce an adaptive response, protecting muscle against further damage during similar subsequent bouts (McHugh et al. 1999). The mechanism of this process is unknown, although removal/repair of 'weak fibres' and/or strengthening of cell membranes may play a role (McHugh et al. 1999). Dietary vitamin E and C supplementation may also limit exercise-induced damage (Evans, 2000). Therefore, the aim of our study was to investigate the adaptation of skeletal muscle following repeated eccentric exercise, while in combination with vitamin supplementation, in the human quadriceps group. The Human Research Ethics Committee, Trinity College, granted ethical approval for this study. Fourteen healthy female subjects (mean ± S.D.; 21.8 ± 0.8 years, 61.6 ± 7.2 kg) were randomly assigned to a control (CON; n = 7) or treatment (TR; n = 7) group. Following familiarisation to all procedures, subjects performed downhill walking (90 min, 15 deg, 5 km h-1) twice, separated by 5 weeks. In the week following each bout, maximal isometric strength (MVC), serum creatine kinase (CK) and muscle soreness (DOMS) were measured on days 1, 2, 3 and 7. Four weeks prior to bout 2, TR received vitamin E and C at 536 and 1000 mg daily. Following bout 2, both CON and TR received vitamins for the 1 week recovery period. Repeated measures ANOVA, post-hoc and Student's t tests were performed on data. Following bout 1, typical responses to muscle injury were seen. MVC decreased to 82 % (CON) and 72 % (TR), CK increased to 250 % (CON, baseline value, mean ± S.E.M.: 132 ± 47 µmol min-1 l-1) and 450 % (TR, baseline value, 39 ± 7 µmol min-1 l-1) and DOMS increased. These changes peaked on days 1 and 2, returning to normal values by day 7. Following bout 2, an adaptive response was observed with no significant changes in MVC or CK in CON or TR, despite an increase in DOMS in CON (P < 0.001). Interestingly, an increase of 18 % in MVC in TR was seen on day 7 (P < 0.01). The increase in MVC in TR on day 7 suggests vitamin supplementation before bout 2 enhanced the adaptive effect of skeletal muscle to unaccustomed eccentric exercise, after a second bout. Prevention of muscle damage by enhancement of various processes, such as free radical scavenging and/or stabilisation of cell membranes, particularly by vitamin E, may be responsible for this effect. More investigation is needed to further understand the mechanisms responsible for the enhanced effect of vitamin supplementation.